Nighttime Sleep, Chinese Afternoon Nap, and Mortality in the Elderly - Lan, Tzuo-Yun (Associated Professional Sleep Societies, LLC, 2007)
STUDY OBJECTIVES: Although many epidemiologic studies have shown that both short and long nighttime sleep durations are associated with increased mortality in the general population, limited data have been reported for older persons, especially those taking afternoon nap. Data from a prospective cohort study of the elderly in Taiwan were used to examine the relationship among nighttime sleep, Chinese afternoon nap, and mortality. DESIGN: Prospective cohort study SETTING: General population PARTICIPANTS: A nationally representative sample of 3079 Taiwanese community residents aged 64 and over was studied, using reported sleep related information collected in 1993 and subsequent 10-year mortality data. INTERVENTIONS: None MEASUREMENTS AND RESULTS: Cox proportional hazards models, separated by sex, were computed to estimate mortality hazard ratios in relation to nighttime sleep duration and afternoon nap duration, adjusting for potential confounders. Compared to older adults sleeping 7~7.9 hours at night, those with longer sleeping time (≥ 10 hours in males and ≥ 8 hours in females) had a significantly higher risk of total mortality. Afternoon nap alone was not associated with total mortality. When nighttime sleep duration and afternoon nap duration were considered together by adding the interaction term in the model or stratifying sleep hours and nap duration, the effect of afternoon nap on mortality risk remained insignificant. CONCLUSIONS: Longer nighttime sleep duration increases mortality risk in older adults. Chinese afternoon nap is not an independent predictor of mortality. There is no significant benefit or harm of practicing afternoon nap in addition to the regular night sleep on elderly mortality. CITATION: Lan TY; Lan TH; Wen CP; Lin YH; Chuang YL. Nighttime sleep, chinese afternoon nap, and mortality in the elderly. SLEEP 2007;30(9):1105-1110.